KINETICS OF VEGETABLE WASTE DECOMPOSITION USING FISH VISCERA EXTRACT AND BANANA PSEUDOSTEM IN THE COMPOSTING PROCESS - Purnamasari, Syafta Indah; Rachmanto, Tuhu Agung (Lingkar: Journal of Environmental Engineering, 2025)
This study investigated the effectiveness of the Takakura bin method for composting household vegetable waste using Fish Offal MOL and Banana Stem MOL as bioactivators. The Takakura method is a simple, aerobic composting technique that utilizes locally available materials—such as fermented microbial solutions and organic matter—to accelerate decomposition under controlled conditions, producing compost safely within a confined bin. The Carbon-to-Nitrogen ratio (C/N), a key indicator of compost maturity, represents the balance between carbon (energy source for microbes) and nitrogen (essential for microbial growth). Optimal composting typically occurs when the C/N ratio decreases from around 25–30:1 to below 20:1, indicating efficient organic matter breakdown. Results showed that compost pH remained between 6.0–7.5 and temperature between 25–30°C, ideal for mesophilic microbial activity. Both MOL treatments enhanced microbial diversity—Bacillus spp. dominated as primary decomposers, while Lactobacillus spp. in Fish Offal MOL helped lower pH and inhibit pathogens. The composting efficiency improved significantly, with faster C/N reduction, greater weight loss, and shorter maturation time. The Fish Offal and Banana Stem MOL bioactivators achieved over 80–90% efficiency in accelerating decomposition, producing mature compost with dark color, earthy odor, and fine texture. These findings confirm that the Takakura bin method, enhanced with MOL bioactivators, provides a highly efficient and eco-friendly solution for household organic waste management.